Government involvement in vocational training during the COVID-19 pandemic – the case of Israel - Bental, Benjamin [Verfasser]; Weinreb, Alex [Verfasser]; Weiss, Avi [Verfasser] (My University, 2022)
„Vocational Training in Israel is sponsored and monitored through a complicated web of government ministries and agencies. In response to the COVID-19 crisis, which dramatically increased the number of workers who were separated from their jobs, the government initiated a large programme that included, among other things, funds for Vocational Training. However, due to the complexity of the system, only about a third of the allocated amount was utilized, which is reflected in the small number of workers who have actually been retrained. Currently, an ambitious training programme of the Innovation Authority is underway, providing technical skills to about 6,000 workers.“ (authors’ abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.3.4 Asien; 370; 330; Berufsbildungssystem; Berufsausbildung; Pandemie; Berufsbildungspolitik; Ausbildungsförderung; Arbeitslosigkeit; Quantitative Angaben; Israel